(untitled) (Research, Society and Development, 2021)
The aimed of the study was to evaluate the effect of continuous artificial aeration on zootechnical performance, hematological characteristics and glucose concentration of tambaqui (Colossoma macropomum) cultivated in a system without water flow. The study was conducted with two treatments, with aeration and without artificial aeration. Were 600 tambaqui juveniles with an average initial weight of 15 ± 0.15g were distributed in two excavated tanks. Thirty fish were captured per cultivation unit to perform monthly biometric measurements and were subjected to blood collection to determine hematological parameters. There was no difference between hematological variables (p<0.05). However, the continuous use of artificial aeration provided fish with more comfortable conditions, resulting in greater performance (p<0.05) in up to 90 days of cultivation, with an average daily weight gain of 4.82 g compared to 4.49g to the system without artificial aeration. It can be inferred that fish grown in a system without artificial aeration presented, when compared to those raised in a system with continuous artificial aeration, smaller values (p<0.05) of growth, both in weight and in length, consequently the continuous use of the aerator provided favorable conditions for the fish, resulting in average daily weight gain and total biomass gain.